(untitled) (Research, Society and Development, 2019)
In the last decades, civil construction has been engaged to implement a series of initiatives aimed at modernizing urban infrastructure and promoting better environmental, social and economic conditions that translate into competitiveness for the sector. This article seeks through a comprehensive bibliographic analysis to better understand what technologies are being employed in building construction to promote the intelligent use of natural resources in both developing and developed countries. As a result, the main methods for better use of energy, water, and the effect that so-called "green" techniques have on the cost reduction of the enterprise are presented. The data on environmental impact, the importance of recycling and reuse of construction waste and the positive impact that the different certifications can bring to the projects are displayed. Knowledge of the technologies raised in this review may encourage industry practitioners and stakeholders to put in place sustainable building actions.